Cloud asset for urban flood control. Issue 3 (August 2015) - Xu, Gangyan; Huang, George Q.; Fang, Ji
Highlights The concept of "cloud asset" is first proposed for urban flood control. The framework of cloud asset is worked out from both hardware and software aspects. Cloud asset enabled workflow management is presented. A case is given to verify the effectiveness of cloud asset.